(untitled) (Asian Journal of Pharmaceutics (AJP), 2026)
Introduction: Emergency medicine (EM) is a relatively new but rapidly expanding specialty in Saudi Arabia. However, research into the specific factors influencing Saudi medical students’ decision to pursue EM remains limited. Objectives: The main objective of this study is to identify and evaluate the factors influencing Saudi medical students’ choice of EM as a future specialty. Materials and Methods: This study was a cross-sectional study conducted from July 2025 to December 2025. A validated, self-administered questionnaire was distributed to a representative sample of medical students aged 18 and above across public and private universities in Saudi Arabia. The questionnaire covered demographic data, exposure to EM, lifestyle perceptions, role models, and personality traits. The target sample size was 384, calculated using Raosoft, and the data were analyzed using the Statistical Package for the Social Sciences version 25.